2020
DOI: 10.3390/medicina56100547
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Freezing Cryopreservation Ensures High Ovarian Tissue Quality Followed by In Vivo and In Vitro Methods and Is Safe for Fertility Preservation

Abstract: Background and objectives: Cancer incidence is growing with younger patients diagnosed with this disease every year. Improved cancer diagnostics and treatment lead to better survival of cancer patients. However, after aggressive chemo- or radiotherapy, cancer survivors suffer from various degrees of subfertility or infertility. Several fertility preservation technologies have been developed for young cancer patients: cryopreservation of germ cells, embryos, or reproductive tissues. The best results have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Differentiation between, and assessments of, cell viability vs. vitality are also of critical interest in other fields of biology, such as in the assessment of yeast cells (29,30), stem cells (31), and ovarian tissue after cryopreservation (32). It is important that the terms ''vitality'' and ''viability'' be used and applied properly for the sake of scientific clarity, consistency, and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation between, and assessments of, cell viability vs. vitality are also of critical interest in other fields of biology, such as in the assessment of yeast cells (29,30), stem cells (31), and ovarian tissue after cryopreservation (32). It is important that the terms ''vitality'' and ''viability'' be used and applied properly for the sake of scientific clarity, consistency, and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Roughly 50% of the cortex from one ovary is surgically removed, dissected, and cryopreserved for future use ( 82 , 83 ). The ovarian tissue is cryopreserved by either slow freezing ( 84 86 ) or vitrification ( 87 ). When a patient intends to restore ovarian function and/or fertility, the cryopreserved tissue can be thawed and replaced ( Figure 1B ).…”
Section: Available Options For Fertility Preservationmentioning
confidence: 99%
“…For OTC, recent advances allow examination of tissue vitality; structural, functional, and DNA integrity; malignant cell contamination; and detection of molecular tumor markers [ 231 ]. One study reported that the implementation of a new miRNA array test in the slow-freezing protocol could yield a rate of human ovarian tissue with no structural damage as high as 80% [ 232 ].…”
Section: Future Perspectives Of Fpmentioning
confidence: 99%